Gendered work norms in Egypt: Evidence on preferences and social perceptions - Allen IV, James; Gilligan, Daniel O.; Kurdi, Sikandra; Shokry, Nada; Yassa, Basma (International Food Policy Research Institute, 2025)
We examine the nature and scope of gendered work norms in Egypt using new experimental evidence from a household survey. Societal norms around work, care responsibilities and the types of jobs women and men can hold can have a profound effect on gender differences in employment, earnings and life satisfaction. Indeed, while lack of childcare and secure transportation remain widely cited constraints to women’s employment in low-income settings, descriptive and experimental evidence also suggest that deeply rooted social norms about gender roles play a prominent role in driving the persistence of such barriers and in how households evaluate women’s work. Norms emphasizing men as primary breadwinners and women as primary caregivers shape both economic decisions and perceptions of behavior in ways that may limit women’s labor force participation even when opportunities exist.